A Display Simulation Toolbox for Image Quality Evaluation - Farrell, J.; Ng, G.; Ding, Xiaowei; Larson, Kevin; Wandell, B. (IEEE\/OSA Journal of Display Technology, 2008)
The output of image coding and rendering algorithms are presented on a diverse array of display devices. To evaluate these algorithms, image quality metrics should include more information about the spatial and chromatic properties of displays. To understand how to best incorporate such display information, we need a computational and empirical framework to characterize displays. Here we describe a set of principles and an integrated suite of software tools that provide such a framework. The display simulation toolbox (DST) is an integrated suite of software tools that help the user characterize the key properties of display devices and predict the radiance of displayed images. Assuming that pixel emissions are independent, the DST uses the sub-pixel point spread functions, spectral power distributions, and gamma curves to calculate display image radiance. We tested the assumption of pixel independence for two liquid crystal device (LCD) displays and two cathode-ray tube (CRT) displays. For the LCD displays, the independence assumption is reasonably accurate. For the CRT displays it is not. The simulations and measurements agree well for displays that meet the model assumptions and provide information about the nature of the failures for displays that do not meet these assumptions.